Endovascular Biopsy of Vertebrobasilar Aneurysm in Patient With Polyarteritis Nodosa - Narsinh, Kazim H.; Narsinh, Kamileh; McCoy, David B.; Sun, Zhengda; Halabi, Cathra; Meisel, Karl; Tihan, Tarik; Chaganti, Krishna; Amans, Matthew R.; Halbach, Van V.; Higashida, Randall T.; Hetts, Steven W.; et al. (Frontiers in Neurology, 2021)
Background and Purpose: Management of unruptured intracranial aneurysms remains controversial. Decisions to treat are heavily informed by estimated risk of bleeding. However, these estimates are imprecise, and better methods for stratifying risk or tailoring treatment strategy are badly needed. Here, we demonstrate an initial proof-of-principle concept for endovascular biopsy to identify key molecular pathways and gene expression changes associated with aneurysm formation. We couple this technique with single cell RNA sequencing (scRNAseq) to develop a roadmap of the pathogenic changes of a dolichoectatic vertebrobasilar aneurysm in a polyarteritis nodosa patient. Methods: Endovascular biopsy and fluorescence activated cell sorting was used to isolate viable endothelial cells (ECs) using established techniques. scRNAseq was then performed on 24 aneurysmal ECs and 23 patient-matched non-aneurysmal ECs. An integrated panel of bioinformatic tools was applied to determine differential gene expression, enriched signaling pathways, and cell subpopulations hypothesized to drive disease pathogenesis. Results: We identify a subset of 7 (29%) aneurysm-specific ECs with a distinct gene expression signature not found in patient-matched control ECs. Gene set enrichment analysis identified these ECs to have increased expression of genes regulating leukocyte-endothelial cell adhesion, major histocompatibility complex (MHC) class I, T cell receptor recycling, tumor necrosis factor alpha (TNFα) response, and interferon gamma signaling. Histopathologic analysis of a different intracranial aneurysm that was later resected yielded a diagnosis of polyarteritis nodosa and positive staining for TNFα. Conclusions: We demonstrate feasibility of applying scRNAseq to endovascular biopsy samples and identify a subpopulation of endothelial cells associated with cerebral aneurysm in polyarteritis nodosa. Endovascular biopsy may be a safe method for deriving insight into disease pathogenesis and tailoring personalized treatment approaches to intracranial aneurysms.